Inclusive land ecological benefits: assessing the eco-efficiency returns of China’s green industrial policy based on a quasi-natural experiment - Li, Yarong; Xiao, Xinyou; Chen, Jiani; Huang, Chunlei (Frontiers in Environmental Science, 2025)
Green industrial policy (GIP) is a crucial instrument for driving a green, low-carbon transition. While prior research has predominantly examined its role in enhancing firms’ green performance, its potential contribution to the ecological transformation of land use has been largely overlooked. This study uses panel data from 287 prefecture-level cities in China over the period 2007–2022 and employs a multi-period difference-in-differences (DID) framework, leveraging the quasi-natural experiment provided by the “Comprehensive Demonstration Cities for Energy Saving and Emission Reduction” pilot program, to investigate the impact of green industrial policy on urban land use eco-efficiency (ULUEE). Our findings show that GIP significantly improves ULUEE, and this result remains robust across various robustness checks. Mechanism analysis indicates that the policy stimulates urban green technological innovation and optimizes the energy consumption structure, both of which contribute to higher ULUEE. Heterogeneity analysis further reveals that the policy’s positive effects are especially pronounced in resource-declining cities, small and medium-sized cities, old industrial base cities, cities with lower levels of scientific and educational development, and cities where public environmental concern is greater. These results imply that the ecological benefits of GIP are broadly inclusive, albeit contingent upon the public’s environmental awareness. By examining GIP through the lens of land use, this paper uncovers its ecological value and offers a novel pathway for enhancing ULUEE.